Early postoperative results after surgical aortic valve replacement concomitant with different methods of myocardial revascularization - K.S. Boyko; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The aim – to analyze the results of the early postoperative period of surgical aortic valve replacement (SAVR) combined with endovascular or surgical methods of myocardial revascularization. Materials and methods. For this retrospective study, a selection of medical records of adult patients (over 18 years of age) who underwent SAVR concomitant with myocardial revascularization in the period from 2018 to 2022 was carried out. Results and discussion. We selected 95 patients who were treated with SAVR with concomitant myocardial revascularization (the first group (n = 31) – a combination of SAVR and percutaneous coronary intervention (PCI); the second group (n = 48) – a combination of SAVR and CABG). In patients of the first group, lesions of the main left coronary artery and the circumflex artery were recorded, respectively, by 24.85 % (p = 0.011) and by 23.7 % (p = 0.033) less often. Moreover, the patients of the first group required intraoperative use of more than two doses of blood red cell mass by 21.4 % less often (p = 0.046). In the early postoperative period, a lower level of bleeding was observed in patients of the first group compared to the second group (180 (150; 250) ml vs. 250 (200; 305) ml, p = 0.008). Conclusions. Patients who underwent PCI before SAVR were characterized by a shorter duration of surgery, cardiopulmonary bypass, and aortic cross-clamping, while no significant difference in major early postoperative complications was observed between the study groups.